Case Report: The Second Near-Infrared Window Indocyanine Green Angiography in Giant Mediastinal Tumor Resection - Mi, Jiahui; Liu, Ganwei; Lu, Liyang; Yang, Feng; Zhao, Hui; Li, Yun; Jiang, Guanchao; Yang, Fan; Hu, Zhenhua; Zhou, Jian (Frontiers in Surgery, 2022)
Giant mediastinal tumors are often accompanied by abundant blood supply and have an unclear border with adjacent vessels, making surgical resection difficult. Failure to distinguish the complex vessels during the operation often results in vascular injury or hemorrhage, which severely increases the operation time and perioperative risk. At present, surgeons can only determine the vessel’s location and course by preoperative imaging and intraoperative exploration in visible light. Therefore, we report a case of a large anterosuperior mediastinal tumor resection assisted by near-infrared (NIR) indocyanine green (ICG) angiography. Furthermore, we applied the second near-infrared window (NIR-II, 1,000–1,700 nm) to detect the fluorescence signals in the clinic for the first time. The NIR-II window is able to explore deeper tissues in centimeters and obtain higher resolution in millimeters than the traditional first near-infrared window (NIR-I, 700–900 nm). Finally, NIR-II ICG angiography shows the clear location and course of the vessels, which can help surgeons reduce unnecessary blood vessel injury and increase the safety of mediastinal tumor resection.